Proceedings of the Ocean Drilling Program 1992
DOI: 10.2973/odp.proc.sr.123.122.1992
|View full text |Cite
|
Sign up to set email alerts
|

Aptian-Albian Foraminifers from Site 766, Cuvier Abyssal Plain, and Comparison with Coeval Faunas from the Australian Region

Abstract: The distribution of 79 foraminiferal species is recorded among 23 samples taken from Cores 123-776A-16R through 123-766A-25R. The benthic species belong to the Ammodiscidae, Ammosphaeroidinidae, Spiroplectamminidae,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…In contrast to this distribution pattern, the Ammobaculites Association (Haig 1979a, b;Haig 1992;Haig & Lynch 1993) inhabited the vast shallow sea that covered much of the interior of Australia during this time. The Ranmoor Member in the northern Eromanga Basin, of equivalent age to the basal Gearle Siltstone, contains an Ammobaculites Association assemblage with some Marssonella Association elements (Haig & Lynch 1993, p. 332-337).…”
Section: Foraminiferal Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to this distribution pattern, the Ammobaculites Association (Haig 1979a, b;Haig 1992;Haig & Lynch 1993) inhabited the vast shallow sea that covered much of the interior of Australia during this time. The Ranmoor Member in the northern Eromanga Basin, of equivalent age to the basal Gearle Siltstone, contains an Ammobaculites Association assemblage with some Marssonella Association elements (Haig & Lynch 1993, p. 332-337).…”
Section: Foraminiferal Evidencementioning
confidence: 99%
“…Tethyan planktonic genera such as ~cinella and Biticinella are absent from these faunas, and this probably reflects cool surface waters (Haig 1979a(Haig , b, 1992. On the adjacent continental margin (at Ocean Drilling Program Site 766), Haig (1992) demonstrated that foraminiferal species with tethyan affinities first appeared in the oceanic plankton during the latest Albian, reflecting a significant warming of surface waters during this time. A similar change was recorded by Haig & Lynch (1993) on the New Guinea margin of the continent.…”
Section: Foraminiferal Evidencementioning
confidence: 99%
See 3 more Smart Citations